2016
DOI: 10.1021/acsphotonics.6b00436
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light Metasurfaces Based on Single-Crystal Silicon

Abstract: Semiconducting nanostructures are promising as components in high-performance metasurfaces. We show that single-crystal silicon can be used to realize efficient metasurface devices across the entire visible spectrum, ranging from 480 to 700 nm. Alternative forms of silicon, such as polycrystalline and amorphous silicon, suffer from higher absorption losses and do not yield efficient metasurfaces across this wavelength range. To demonstrate, we theoretically and experimentally characterize the resonant scatteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 37 publications
1
80
0
Order By: Relevance
“…A 79% measured transmission efficiency is reported for the metasurface lens with a 0.86 numerical aperture [68]. Several dielectric materials have been used for metasurface demonstration at visible, including silicon (in amorphous, poly, or single crystalline form) [33,128,230,231], gallium nitride [73,161], silicon nitride [69,194,196], titanium dioxide [6,71,77], and silicon dioxide [232]. Figure 6d shows experimental results of a metasurface OAM generator designed at 532-nm wavelength for underwater optical communications.…”
Section: A Wavefront Shapingmentioning
confidence: 99%
“…A 79% measured transmission efficiency is reported for the metasurface lens with a 0.86 numerical aperture [68]. Several dielectric materials have been used for metasurface demonstration at visible, including silicon (in amorphous, poly, or single crystalline form) [33,128,230,231], gallium nitride [73,161], silicon nitride [69,194,196], titanium dioxide [6,71,77], and silicon dioxide [232]. Figure 6d shows experimental results of a metasurface OAM generator designed at 532-nm wavelength for underwater optical communications.…”
Section: A Wavefront Shapingmentioning
confidence: 99%
“…Starting from a random, continuous refractive index distribution bounded by the indices of air and the dielectric (nd), structures satisfying the desired performance but with binary indices 1 and nd can be achieved by using gradient-based optimization algorithms. Sell et al reported an approach for designing periodic silicon metasurfaces with multiwavelength functionalities [83][84][85][86]. When the target was set to deflect light of discrete wavelengths to different diffraction orders, an FOM involving all the diffraction efficiencies was defined for optimization.…”
Section: Nanophotonic Design Based On Optimization Techniquesmentioning
confidence: 99%
“…To simplify our analyses, we have dropped the imaginary part of the refractive index when designing and evaluating our devices. In the future, we will expand the database to include a wider scope of materials, including other variants of silicon, such as crystalline [37] and amorphous silicon [38], as well as titanium dioxide [39,40] and silicon nitride [41,42], which are commonly used for visible light applications. We will also include devices with more diverse functionalities, such as polarization control, as well as wavelength-scale scattering elements that can be stitched together to create aperiodic structures [19].…”
Section: Metagrating Standardization and Categorizationmentioning
confidence: 99%